Fighting multiple tax havens - May Elsayyad; Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper develops a competition theory framework that evaluates an important aspect of the OECD's Harmful Tax Practices Initiative against tax havens. We show that the sequential nature of the process is harmful and more costly than a 'big bang' multilateral agreement. The sequentiality may even prevent the process from being completed successfully. Closing down a subset of tax havens reduces competition among the havens that remain active. This makes their 'tax haven business' more profitable and shifts a larger share of rents to these remaining tax havens, making them more reluctant to give up their 'tax haven business'. Moreover, the outcome of this process, reducing the number of tax havens, but not eliminating them altogether, may reduce welfare in the OECD.
Keywords: F21; H26; H77; H87; 330; tax haven; harmful tax practices; bidding for haven inactivation; Steueroase; Steuerwettbewerb; Steuerpolitik; OECD-Staaten-seitig; Steuerflucht; Kritik; Welt; OECD-Staaten